DEVELOPING BASIC ENGLISH COURSEBOOK LEVEL 1 FOR UNIVERSITY STUDENTS AT STKIP AGAMA HINDU SINGARAJA - Ni Putu Tasya Aurellia Putri; I Luh Ariss Susanti; Pande Gede Artha Pratama (JR-ELT (Journal of Research in English Language Teaching), 2026)
This research aims to develop a Basic English Coursebook Level 1 for university students at STKIP Agama Hindu Singaraja. The background of this research is the absence of a standardized and needs-based coursebook, which results in less systematic and less effective teaching and learning processes. This research employed Design and Development Research (DDR) using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The data were collected through interviews, observations, and expert validation. The findings show that the developed coursebook contains structured, contextualized, and learner-centered materials that integrate the four language skills, namely listening, speaking, reading, and writing, along with grammar and vocabulary development. Based on the validation results from two expert judges, the product is categorized as highly feasible to be used as teaching material. Furthermore, the coursebook is considered effective in supporting students’ engagement and motivation in learning Basic English. Therefore, this developed coursebook is expected to serve as a solution to enhance the quality of Basic English teaching in higher education, particularly at STKIP Agama Hindu Singaraja.